Analysis of pedestrian-to-ground impact injury risk in vehicle-to-pedestrian collisions based on rotation angles. (February 2018) - Shi, Liangliang; Han, Yong; Huang, Hongwu; Li, Quan; Wang, Bingyu; Mizuno, Koji
Abstract: Introduction: Due to the diversity of pedestrian-to-ground impact (secondary impact) mechanisms, secondary impacts always result in more unpredictable injuries as compared to the vehicle-to-pedestrian collisions (primary impact). The purpose of this study is to investigate the effects of vehicle frontal structure, vehicle impact velocity, and pedestrian size and gait on pedestrian-to-ground impact injury risk. Method: A total of 600 simulations were performed using the MADYMO multi-body system and four different sizes of pedestrians and six types initial gait were considered and impacted by five vehicle types at five impact velocities, respectively. The pedestrian rotation angle ranges (PRARs) ( a, b, c, d ) were defined to identify and classify the pedestrian rotation angles during the ground impact. Results: The PRARs a, b, and c were the ranges primarily observed during the pedestrian landing. The PRAR has a significant influence on pedestrian-to-ground impact injuries. However, there was no correlation between the vehicle velocity and head injury criterion (HIC) caused by the secondary impact. In low velocity collisions (20, 30 km/h), the severity of pedestrian head injury risk caused by the secondary impact was higher than that resulting from the primary impact. Conclusions: The PRARs defined in this study are highly correlated with the pedestrian-to-ground impact mechanism, and can be used to further analyze the pedestrian secondary impact and to predict the head injury risk. Practical applications: To reduce the pedestrian secondary impact injury risk, passive and active safety countermeasures should be considered together to prevent the pedestrian's head-to-ground impacts, particularly in the low-velocity collisions. Highlights: Pedestrian rotation angle ranges were defined to categorize the Pedestrian landing mechanisms during the secondary contact to the ground in vehicle to pedestrian collisions. The pedestrian rotation angle ranges shows a good assessment of the pedestrian-to-ground impact injury risk. It was found that there was no obvious correlation between the vehicle velocity and HIC (ground) score, but the HIC (car) score was significantly correlated with vehicle velocity.